2022
DOI: 10.3390/vaccines10020310
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of COVID-19 Infection among Patients with Diabetes and Their Vaccination Coverage Status in Saudi Arabia: A Cross-Sectional Analysis from a Hospital-Based Diabetes Registry

Abstract: Patients with diabetes have a higher risk of severe infection and mortality due to COVID-19. Considering the current limited effective pharmacological treatments, vaccination remains one of the most effective means to control the pandemic. The current study aimed to determine the prevalence of COVID-19 infection and the rate of COVID-19 vaccination coverage among patients with type 2 diabetes mellitus. The patients were identified from a diabetes hospital registry at Prince Sultan Military Medical City, Riyadh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 82 publications
1
10
3
Order By: Relevance
“…COVID-19 vaccination uptake was especially low among those with chronic DM complications (11.2%). The uptake rate among all participants was much lower than that observed among people with DM in other countries (e.g., 84.8% of people with DM in Saudi Arabia received at least one dose of COVID-19 vaccination) [ 25 ]. At the time of study, China was hit by the pandemic caused by Omicron sub-variant BA.2 of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…COVID-19 vaccination uptake was especially low among those with chronic DM complications (11.2%). The uptake rate among all participants was much lower than that observed among people with DM in other countries (e.g., 84.8% of people with DM in Saudi Arabia received at least one dose of COVID-19 vaccination) [ 25 ]. At the time of study, China was hit by the pandemic caused by Omicron sub-variant BA.2 of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, three studies have investigated actual uptake of COVID-19 vaccination among people with DM. The prevalence of uptake was 21.5% in India [ 23 ], 25.2%% in China [ 24 ], and 84.8% in Saudi Arabia [ 25 ]. The main reasons for vaccine hesitancy among people with DM included concerns about vaccine safety and side effects, perceived consequences of COVID-19 infection, relatives’ vaccination status, and suggestions made by physicians [ 4 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors such as lack of awareness, vaccine efficacy, and safety (side effects) contribute to the reluctance to be vaccinated [ 56 ]. The other cross-sectional study found that vaccination remains one of the most effective means to control the pandemic [ 57 ]. T2DM patients with no previous history of COVID-19 infection were more likely to be fully vaccinated (i.e., receiving two doses) than those with a previous history of the infection—63.9% versus 14.6%, respectively [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The other cross-sectional study found that vaccination remains one of the most effective means to control the pandemic [ 57 ]. T2DM patients with no previous history of COVID-19 infection were more likely to be fully vaccinated (i.e., receiving two doses) than those with a previous history of the infection—63.9% versus 14.6%, respectively [ 57 ]. The pandemic has led society to rethink the past and to adapt and live in a completely different way.…”
Section: Discussionmentioning
confidence: 99%